THE CONCEPT OF PROFESSIONAL COMPETENCE DEVELOPMENT OF TEACHING STAFF AT VOCATIONAL COLLEGES (Innovative professional education, 2024)
Awareness of the key role of the teacher in the process of vocational training at colleges determines the need for continuous purposeful development of the professional competence of the college teacher. The starting points for the concept of the development of professional competence of teaching staff at vocational colleges were the humanization of the educational process and the theoretical and methodologicalfoundations of continuous professional education. The concept was focused on the development of structuralcomponents of a teacher’s professional competence, as an integrative property of the individual (Motivation andValue, Cognitive-information, Behaviour and Activity, Personal Reflection, Emotion and Volition); as well as onthe development of the main types of teacher’s professional activity at a vocational college (educational,methodical, subject, informational and digital, environmental, inclusive, research and communicativecompetences).
Keywords: vocational higher education, teacher's professional competence, pedagogical skill, professional development